Kristus Dalam Nubuatan Perjanjian Lama - Sunkudon, Pieter G.O. (Sekolah Tinggi Teologi Injili Indonesia Palu, 2023)
There are so many prophecies about the Messiah/Christ in the Old Testament. This fact is very reasonable, considering the entire Bible message is centered on the promise of restoration through Christ. Understand the fundamental interests of the prophecies about Christ can be said to be urgent, because it relates to one of the fundamental doctrines of Christianity. This descriptive article discusses the Old Testament prophecies concerning the Messiah/Christ completely fulfilled in Jesus.